UPAYA MENINGKATKAN HASIL BELAJAR PJOK MATERI TENIS MEJA MELALUI MEDIA DINDING PADA SISWA KELAS VII.4 SMPN 3 SELAT TAHUN PELAJARAN 2019/2020 - Mardiyanto Mardiyanto (JURNAL ILMIAH EDUNOMIKA, 2021)
The background of this research is that there are still many students who have not been able to do the basic techniques of playing table tennis, besides that many students have not yet completed the Minimum Completion Criteria (KKM) with a score of 70.The formulation of the problem based on the background is as follows: Is the application of wall media can improve the results of learning table tennis in class VII.4 SMPN 3 Selat. The purpose of this study was to determine: the improvement of learning outcomes in table tennis for VII.4 grade students of SMPN 3 Selat through the application of modified learning tools. This research is a classroom action research conducted in two cycles. Each cycle has 4 steps, namely: planning, implementing, observing, and reflecting. The data source of this research was students of Class VII.4 SMPN 3 Selat, totaling 30 people consisting of 13 male students and 17 female students. Data collection techniques using observation, ability tests and learning outcomes to play table tennis. Data collection techniques using observation, ability tests and learning outcomes to play table tennis. The data analysis technique used in this research is qualitative descriptive statistics. Based on the results of the study, learning through the application of modified learning tools can improve learning outcomes of table tennis in class VII.4 students of SMPN 3 Selat. From the results of the analysis obtained a very significant increase from cycle I and cycle II. The learning outcomes in the first cycle in the complete category were 41.94% and in the second cycle there was an increase in student learning outcomes in the complete category by 87.10%. So it can be concluded that learning table tennis through wall media can improve student learning outcomes at SMPN 3 Selat. From the analysis results obtained a significant increase from cycle I and cycle II. Some suggestions, especially for SMPN 3 Selat teachers are as follows: teachers should be more innovative in delivering learning material. Teachers should provide learning to students with simple games but contain material elements, so that students are not bored in following the lesson. The teacher should provide a simple, efficient, effective, and cost-effective modification of learning tools to make it visible or held directly by students, because it can motivate students to always try and repeat it continuously